THE ANALYSIS OF LANGUAGE MAINTENANCE OF BATAK TOBA AND KARO LANGUAGE - Maria Friska Nainggolan; Mei Lyna Girsang (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Language maintenance is one of the efforts that can be done to keep regional languages from extinction. The purpose of this study is to determine the level of language maintenance of Batak Toba and Karo languages of middle age teenager of 15-18 years at Kwala Bekala District, Medan. The method used in collecting data is the ‘cakap semuka technique’ using a questionnaire distributed to informants and continued with interview. This research data assessment method uses quantitative methods and the data is analyzed using sociolinguistic theory. From the results of the study it was found that the maintenance of Batak Toba Language among middle age teenager of 15-18 year old at Kwala Bekala district XVII was (30 %) and the maintenance of Karo Language of middle age teenager of 15-18 at Kwala Bekala district XVII was (58 %). It can be concluded that the maintenance of Karo language among middle age teenager of 15-18 years old is higher than the maintenance of Batak Toba language among middle age teenager of 15-18 years at Kwala Bekala Medan.